Experiential and Persistent Entrepreneur : Deepak Jain From Subtlelabs - Kar, Brajaballav; Pathak, Mallika Devi; Panda, Madhu Chhanda (AMC Indian Journal of Entrepreneurship, 2019)
Every entrepreneur has a unique story to tell. The uniqueness comes from background, entrepreneurial intention, individual resource base, execution efforts, initial failures, learning and subsequent sustainability. Entrepreneurship literature identifies various motivation factors for entrepreneurial venture creation; however, none of those predict venture formation on an isolated basis. It is an interplay of multiple factors, whose interaction is not known precisely. Thus, it is imperative that each entrepreneurial effort is captured and interaction nuances are understood for analysis. An entrepreneur rarely does a classical market analysis of size and growth before selecting the product or service offering; such market analysis may be expensive, time consuming, and out of reach for an individual entrepreneur. Thus, more often innovation or identification of niche segment is due to serendipity. Finding the opportunity and innovating products or services for market gap become a continual and experiential process. The entrepreneur has to continually discover market gap and shift strategies to persist and survive. This case study presents an entrepreneur who used his self-efficacy and persistence to create and sustain a service organization. Though in many cases peer-network becomes instrumental in formation and support, such support may not persist for long. The broad environment related to job market and specific situation of the individual also abet entrepreneurial decision. Further, such decisions are evaluated on the basis of self-efficacy. Persistence is also to an extent determined by self-efficacy. The case may be generic to many entrepreneurial efforts in Information Technology (IT) industry segment.